Job Stability Trends, Layoffs, and Transitions to Unemployment : An Empirical Analysis for West Germany - Annette Bergemann; Antje Mertens (Institute for the Study of Labor (IZA), 2004)
This paper studies the evolution of job stability in West Germany. Using data from the German Socio-Economic Panel, we first show that the median elapsed tenure declined for men between 1984 and 1999. Second, estimating proportional Cox hazard models with competing risks and controls for stock sampling, we are able to distinguish the reasons for job separation and different transition states. We show that the decline in the stability of men?s jobs can be attributed partly to an increase in layoffs and partly to an increase in transitions to unemployment. However, these two developments are not significantly related to each other. Some evidence is presented that downsizing of large firms might be responsible for part of the decline in job stability.
Keywords: J63; C41; 330; job stability; labor mobility; layoffs; duration analysis; Arbeitsplatzsicherung; Betriebszugehörigkeit; Arbeitsmobilität; Kündigung; Schätzung; Deutschland